1997
DOI: 10.1159/000190241
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Renal Function in Obstructive Jaundice: Roles of the Thromboxane and Endothelin Systems

Abstract: Patients with intra- or extrahepatic bile-duct obstruction are susceptible to acute renal failure (ARF) especially when undergoing major surgery. We observed in jaundiced rats 4 days after bile-duct ligation (BDL) a decrease in GFR accompanied by polyuria which is associated with increased urinary thromboxane (TX) excretion and glomerular TXB2 synthesis. The TXA2/ PGH2 receptor antagonist daltroban normalized GFR but not urine concentration. There was also a rise in plasma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Extrahepatic cholestasis induces a complex series of hormonal changes in kidneys, [1][2][3][4] which might influence the regulation of OAT1 and OAT3. Likely several local and systemic factors are produced at the same time, and the role of such factors in the regulation of channels and transporters in the presence of BDL is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrahepatic cholestasis induces a complex series of hormonal changes in kidneys, [1][2][3][4] which might influence the regulation of OAT1 and OAT3. Likely several local and systemic factors are produced at the same time, and the role of such factors in the regulation of channels and transporters in the presence of BDL is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Extrahepatic cholestasis refers to obstruction of large bile ducts outside the liver, for instance, due to gallstones. [1][2][3][4] Kidney and liver eliminate numerous potentially toxic xenobiotics, including drugs, toxins, and endogenous metabolites. In some cases, the loss of one route of elimination can be compensated for by the other.…”
mentioning
confidence: 99%
“…tubular brush border vesicles 16,18 , which also could represent one of the mechanisms for decreased fluid and sodium reabsorption in proximal and also in distal nephrons segment 18 . Rodrigo et al 19 suggested that the renal compromise of obstructive jaundice is characterized by changes in the tubular handling of electrolytes.…”
Section: Renal Morphologymentioning
confidence: 99%
“…In some cases, the loss of one route of elimination can be compensated by another [24][25][26] . It must also be mentioned that impairment of liver or kidney functions can cause syndromes characterized by injury of the alternative elimination organ [24,27,28] . For example, prolonged cholestasis, characterized by retention of bile compound, may cause renal damage (reduction in renal hemodynamics, impairment of renal excretion of water and salts, and sensitization of the kidney to anoxia damage), which sometimes leads to renal failure.…”
Section: Cholestasis and Renal Damagementioning
confidence: 99%